Infrastructure Provision as a Catalyst for Local Economic Development in South Africa (The Strategic Review for Southern Africa, 2020)
Throughout the era of the apartheid, the provision and accessibility of infrastructure in South Africa was skewed, and while the minority had access, the majority was overlooked. Local economic development (LED) has rested on the premise that the availability of infrastructure is likely to spur socio-economic development and to lift millions of South Africans out of poverty. However, with South Africa’s economy struggling to register consistent growth, there are difficulties accessing the much-needed finances needed to invest in infrastructure to spur LED. The study that this paper reflects upon used a qualitative research method and a systematic review of the literature relating to infrastructure provision and local economic development. It utilised thematic content analysis to deduce its findings with the hope of bringing in meaning to the overall content of the paper. The study revealed that indeed infrastructure provision is key to local economic development, that South Africa’s infrastructure provision is still skewed as urban areas continue receiving priority over rural areas; that local economic development is key in reducing inequality and spurring economic growth and sustaining the livelihoods of rural dwellers. However, limited investments in infrastructure in rural areas hinder the realization of such benefits. It recommends that the government prioritise LED in rural areas among other suggestions.